2016
DOI: 10.1111/bcp.13048
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of cyclooxygenase‐2 inhibitors: a mechanistic and clinical perspective

Abstract: This article is part of a joint Themed section with the British Journal of Pharmacology on Targeting Inflammation to Reduce Cardiovascular Disease Risk: a Realistic Clinical Prospect? The rest of the Themed section will appear in a future issue of BJP and will be available at http://onlinelibrary.wiley.com/journal/10.1111/(ISSN)1476-5381 Prostaglandin (PG) H synthase 2 [also referred to colloquially as cyclooxygenase (COX) 2] represents a key enzyme in arachidonic acid metabolism in health and disease. It is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(82 citation statements)
references
References 72 publications
5
74
1
2
Order By: Relevance
“…Cyclooxygenase-2 (COX-2) is an inflammatory signal-induced key enzyme in arachidonic acid metabolism, being induced in normal cell types, including blood-derived macrophages, microglia, and endothelial cells in response to inflammatory cytokines (Patrono, 2016). COX-2 expression in ischemic tissue is quickly up-regulated after tMCAO together with MMP-2 and MMP-9 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclooxygenase-2 (COX-2) is an inflammatory signal-induced key enzyme in arachidonic acid metabolism, being induced in normal cell types, including blood-derived macrophages, microglia, and endothelial cells in response to inflammatory cytokines (Patrono, 2016). COX-2 expression in ischemic tissue is quickly up-regulated after tMCAO together with MMP-2 and MMP-9 activity.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first demonstration in a large, randomized, double‐blind, placebo‐controlled phase III study that using anti‐cytokine‐based therapies may be a viable approach for secondary prevention of atherosclerosis‐related CVD. This is particularly relevant given that the use of traditional non‐steroidal anti‐inflammatory drugs and coxibs alike is limited by cardiovascular toxicity, as comprehensively discussed by Patrono (). He provides an overview of the cardiovascular effects of COX‐2 inhibitors, with a focus on the mechanisms contributing to the clinical readouts of COX‐2 inhibition.…”
Section: Nomenclature Of Targets and Ligandsmentioning
confidence: 99%
“…The chronic oral administration of non-selective NSAIDs are linked with many gastrointestinal complications like ulceration, bleeding and perforation (Rafaniello et al), while highly selective COX-2 inhibitors (coxibs) are associated with an increased risk of adverse cardiovascular events (Patrono, 2016). However, in our study, it was not observed any side effects of NSAIDs, which can be reasonable explained by the absence of previous systemic disease in patients, the short-term drug intake and no other age-related factors.…”
Section: Nícoli G A; Conte-neto N; Campos J á D B; Cabrini-mentioning
confidence: 99%